BENARKAH KOMPETENSI DAN BUDAYA ORGANISASI AKAN MENINGKATKAN KINERJA KARYAWAN? - Akhri Ramdhani Fauzan; Sri Wiludjeng Sunu Purwaningdyah (Jurnal Manajemen dan Pemasaran Jasa, 2017)
Based on preliminary studies it was found that employee performance has not been optimal. Some of an important factor that was found supposedly competency and organizational culture is an important factor that is most dominant. As a prominent factor of employee performance, organization culture and competency has been given much attention, as well as the influence of competency and organizational culture to employees performance either partially and simultaneously. Research method used in this research descriptive survey and explanatory survey. The sample in this research is employees of PT PLN (Persero) Area Karawang. The sampling technique used is stratified proportional method whereas the method of analysis used is path analysis. The result of research shows that there is a strong correlation among competency and organizational culture. The hypotheses for the partial impact of competency and organizational culture toward employee performance employee are all accepted. Simultaneous influence competency and organizational culture toward performance of employee gives a significant effect.